Collaborative problem solving vs problem-based learning and cognitive styles on students' problem-solving skills and mathematical reasoning abilities - Agus Setiawan; I Nyoman Sudana Degeng; Cholis Sa'dijah; Henry Praherdhiono (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Indonesia continues to face persistent challenges in students’ mathematical problem-solving and reasoning abilities, as reflected in declining international assessment results. These issues indicate a need for instructional strategies that more effectively cultivate higher-order thinking. CPS and PBL are widely used approaches, yet their combined effects with cognitive styles remain underexplored. Aim: This study aims to compare the effectiveness of Collaborative Problem Solving (CPS) and Problem-Based Learning (PBL) on problem-solving and mathematical reasoning abilities, and to examine the role of Field-Independent (FI) and Field-Dependent (FD) cognitive styles, including their interaction with instructional strategies. Method: A quasi-experimental 2×2 factorial design was implemented with 119 seventh-grade students assigned to CPS or PBL and classified into FI or FD groups using the GEFT instrument. Data on problem-solving and reasoning were collected through validated essay tests. MANOVA was used to analyze main and interaction effects. Results: CPS produced significantly higher gains than PBL in both problem-solving and reasoning. FI students outperformed FD students across both strategies. A significant interaction effect was found, showing that FI learners benefit most from CPS, whereas FD learners perform relatively better under PBL, although still below FI peers. Conclusion: CPS offers a more structured and effective pathway for developing higher-order mathematical thinking. Cognitive style strongly influences learning outcomes, highlighting the need for differentiated support. Instructional designs that integrate structured collaboration and cognitive-style profiling are recommended to optimize students’ mathematical problem-solving and reasoning abilities